ANALISIS MODEL PEMECAHAN MASALAH FISIKA DAN KAITANNYA DENGAN KARAKTER BERFIKIR KRITIS DAN HASIL BELAJAR SISWA DI KELAS X SMA N KOTA PADANG - Rahmat Hidayat (PILLAR OF PHYSICS EDUCATION, 2014)
Student`s critical thinking character is still far under the ideal value. This condition is predicted because critical thinking character is not trained during learning process One effort could applied to train student`s critical thinking character by using problem solving model. Therefore researcher explores model of physic problem solving applied in senior high schools and find the connection with student`s critical thinking character and learning outcomes. Kind of research is descriptive ex-post facto. Popullation taken is all of X grader of Senior High Schools in Padang city. Sample is defined by purposive sampling technique and gives SMA N 3 Padang as representative of ex-International Standardized School , SMA N 5 Padang as representative of National Standarized School, and SMA N 12 Padang as representative of Regular School. The instrument in this research are interview form, voice recorder, observation sheet and questionnaire. Data is analyzed by using content analysis to describe model of problem solving. Result of research shows that model of problem solving is depend on curriculum. Ex-International Standardized School has been applying Curriculum 2013, which based on scinetific approach, meanwhile two others are not . Model of physic problem solving based scientific approach can train student`s critical thingking more. Beside that, scientific approach applied in model of phyisc problem solving gives better learning outcomes